State of the Art on Airborne LiDAR Applications in the Field of Forest Engineering - Aricak, Burak; Wing, Michael Gilbert; Akay, Abdullah Emin (Springer Nature, 2023)
Managing forest resources in large landscape can be a highly time- and resource-consuming task requiring significant amounts of data collection in the field. Airborne Light Detection and Ranging (LiDAR) is one of the most effective remote sensing technologies for data collection and is capable of providing quick and accurate 3D point clouds from which vegetative cover and the ground surfaces can be discerned. LiDAR-based 3D point clouds and derivative products are used in a number of forestry activities including forest inventory and management, forest operations, fire modeling and biomass and carbon storage estimations. In particular, high-resolution digital elevation models (DEMs) produced from point clouds can assist forest engineers in performing harvesting planning and forest road design. Also, LiDAR-produced tree lists can be mapped on a DEM and can be used for planning of landing areas, skid roads, and cable corridors. In this chapter, a comprehensive overview to the use of LiDAR technology in the field of forest engineering is discussed by reviewing previously conducted studies. Firstly, basic principles of operating LiDAR technology are provided, and then the progress and opportunities of using LiDAR technology in various forest engineering applications are presented. These applications include 3D forest road design, road geomatics, road construction, earthwork allocation, forest transportation, forest operation, sediment prediction, and logging impact assessment. The results derived from these previous studies suggested that LiDAR technology has the potential to offer highly reliable and accurate 3D surface data when compared to the estimations of ground-based surveys. Thus, airborne LiDAR is a rapidly developing technology which provides a great potential for efficiently performing forest engineering activities quickly and accurately over large landscape areas. © Springer Nature Singapore Pte Ltd. 2022.
Keywords: 3D road design; Airborne LiDAR; Earthwork allocation; Forest operation planning; Impact assessment; Transportation network